The Appropriate Employment Model of Modern Enterprises for Hiring Persons with Disabilities in the Eastern Economic Corridor (EEC) Project - Rodpai, Wanwisa; Kongyoungyune, Rungraditt; Lakul, Jitakorn (Journal of Neonatal Surgery, 2025)
The purposes of this dissertation were: 1) investigate the levels of attitude factors, equity factors, and entrepreneurial participation factors affecting appropriate employment models for people with disabilities 2) study the relationships between attitude factors, equity factors, and entrepreneurial participation factors affecting appropriate employment models for people with disabilities, and 3) examine the direct, indirect, and overall influences of attitude factors, equity factors, and entrepreneurial participation factors on appropriate employment models for people with disabilities. The sample comprises 359 enterprises in the Eastern Economic Corridor (EEC) area. Data collection instruments include questionnaires. Statistical methods used in this research consist of percentage, mean, standard deviation, Pearson correlation coefficient, and path analysis. The findings reveal that 1) the levels of attitudes towards employing people with disabilities, entrepreneurial participation in employing people with disabilities, equity principles in employing people with disabilities, and appropriate employment models for people with disabilities, as measured by organizational effectiveness, are at moderate levels. 2) The Pearson correlation coefficients between attitudes towards employing people with disabilities and equity principles in employing people with disabilities have a high positive correlation with entrepreneurial participation in employing people with disabilities and appropriate employment models for people with disabilities, as measured by organizational effectiveness, with statistical significance at the .01 level. Additionally, all three factors have a high positive correlation with appropriate employment models for people with disabilities, as measured by organizational effectiveness, with statistical significance at the .01 level. 3) Attitudes towards employing people with disabilities and entrepreneurial participation in employing people with disabilities have an overall positive influence on organizational effectiveness. Equity principles in employing people with disabilities and entrepreneurial participation in employing people with disabilities also have an overall positive influence on organizational effectiveness. Although equity principles in employing people with disabilities have no statistically significant direct influence on organizational effectiveness, they have a statistically significant indirect influence through entrepreneurial participation in employing people with disabilities. Thus, equity principles in employing people with disabilities have a combined positive influence on the organizational effectiveness of enterprises employing people with disabilities in the EEC project with statistical significance (TE = 0.47, p < 0.01). Moreover, considering the conceptual framework, the factors of attitudes towards employing people with disabilities, equity principles in employing people with disabilities, and entrepreneurial participation in employing people with disabilities can explain and predict the organizational effectiveness of enterprises employing people with disabilities in the EEC project at 77% (R2 = 0.77).